Comparison of Normal and Abnormal Conditions in ECG Using RR Variablity and Spectral Density - R. Thamizhvani, T; Elsa Joseph, Josline; Babu, Bincy; Rithikka, U; Rohini, D; Josephin Arockia Dhivya, A (International Journal of Engineering and Technology, 2018)
Abnormality of the heart is monitored by Electrocardiograph (ECG). The ECG waveform is formed of PQRS pattern. Differentiation of the abnormalities based on the ECG signal is simple algorithm for diagnosis. ECG data of normal, atrial fibrillation and congestive heart failure is obtained from a authorized database. R peak from the QRS complex is detected using Pan-Tompkins algorithm for analysis. Mean RR and heart rate variability parameters are extracted from the QRS complex detected. With these results, the difference in the three ECG signals can be determined. For further detailed comparison, frequency component variation is analysed using power spectral density. Based on density spectrum, the differentiation of normal and abnormal ECG signals can be determined.Â